2019
DOI: 10.1080/03043797.2019.1646210
|View full text |Cite
|
Sign up to set email alerts
|

Scaffolding interdisciplinary project-based learning: a case study

Abstract: Can you ask students from three different bachelor programmes to help solve planning and routeing problems for hospitals? In the presented case an interdisciplinary approach was shown to be successful after some redesign. Students from Applied Mathematics, Civil Engineering and Industrial & Engineering Management jointly designed solutions for 'traffic' to and through the hospital using stochastic modelling. Importantly this project was scaffolded through coursework, supervision and problemdesign. The particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 13 publications
(15 reference statements)
1
36
0
5
Order By: Relevance
“…Among such alternatives, for university students, active and interdisciplinary project-based learning, where students lead and develop a final project, has been proven useful ( 43 , 44 ), as it promotes critical thinking, practical application of knowledge ( 45 ), and problem-solving skills ( 46 ). Its implementation in the training of health professionals on mental disorders is recent, however it has proven to effectively foster professional skills ( 47 ) and a comprehensive and inclusive understanding of the different social processes involved in mental health outcomes and care ( 48 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among such alternatives, for university students, active and interdisciplinary project-based learning, where students lead and develop a final project, has been proven useful ( 43 , 44 ), as it promotes critical thinking, practical application of knowledge ( 45 ), and problem-solving skills ( 46 ). Its implementation in the training of health professionals on mental disorders is recent, however it has proven to effectively foster professional skills ( 47 ) and a comprehensive and inclusive understanding of the different social processes involved in mental health outcomes and care ( 48 50 ).…”
Section: Introductionmentioning
confidence: 99%
“…Providing students with authentic learning opportunities, though the collaborative learning projects only a short-term program, this study has shown that students can enhance and act on their motivation (Kato, 2016). The results of the study prove that problems in the context of interdisciplinary learning are fundamental and interdisciplinary research in the form of project-based learning has proven successful (MacLeod & van der Veen, 2020). Students from various disciplines (from Mathematics, Civil Engineering, and Industrial Management & Engineering) jointly design solutions for traffic.…”
Section: Resultsmentioning
confidence: 70%
“…Meta-Theme 3). 70,71 SL frames the learning process as a socialization process where students acquire knowledge and expertise through "legitimate peripheral participation", the process of apprenticing someone or some group and learning how to think and behave like those in the same community. This is related to the frequency which students can interact with SynBio educators and synthetic biologists actively researching and working in the field (cf.…”
Section: Design Principle 3: Learning Progressions (Lps)mentioning
confidence: 99%